Linguistics Politeness In Mata Najwa’s Discussion - Dani, Ersika Puspita (Institute of Computer Science (IOCS), 2020)
This qualitative research investigated the discursive struggle utterance in the discussion of Mata Najwa Program. This focused on finding out what kinds of discursive struggle. In conducting this research, having copy the video of Mata Najwa from website, utterance are transcribed, identified, and then analyzed according to Murni’s five strategies (2013: 59) to identify and to interpret the power of speech of Angel Lelga's utterances as a data. For findings, there were five struggles over value of Linguistic Politeness, namely: 5 utterances of Claiming common ground, 4 utterances of bringing forward accurate arguments and data, 3 utterances of minimizing imposition, 3 utterances of asserting reciprocity and 2 utterances of minimizing conflict and confrontation.